2019
DOI: 10.1038/s41398-019-0494-6
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the animal model of bipolar disorder induced by Ouabain: face, construct and predictive perspectives

Abstract: A particular challenge in the development of a bipolar disorder (BD) model in animals is the complicated clinical course of the condition, characterized by manic, depressive and mixed mood episodes. Ouabain (OUA) is an inhibitor of Na + /K + -ATPase enzyme. Intracerebroventricular (ICV) injection of this drug in rats has been regarded a proper model to study BD by mimic specific manic symptoms, which are reversed by lithium (Li), an important mood stabilizer drug. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
39
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 64 publications
(76 reference statements)
4
39
0
2
Order By: Relevance
“…In the rat model, increased locomotor activity 16 and cognitive flexibility impairment 24 were demonstrated as characteristics reflecting the mania-like phase. In a recent study, both the mania-like and the depressive phase were demonstrated in rats, along with the accompanying oxidative stress and Na, K-ATPase dysfunction, the same way as they appear in patients with bipolar disorder 23 . In our mice model of ouabain-induced mania, the mania-like phase is illustrated with hyperlocomotion, stereotyped behavior, and a lessened degree of anxiety.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…In the rat model, increased locomotor activity 16 and cognitive flexibility impairment 24 were demonstrated as characteristics reflecting the mania-like phase. In a recent study, both the mania-like and the depressive phase were demonstrated in rats, along with the accompanying oxidative stress and Na, K-ATPase dysfunction, the same way as they appear in patients with bipolar disorder 23 . In our mice model of ouabain-induced mania, the mania-like phase is illustrated with hyperlocomotion, stereotyped behavior, and a lessened degree of anxiety.…”
Section: Discussionmentioning
confidence: 82%
“…In this model intracerebroventricular (ICV) injection of ouabain instantly caused hyperactivity in rats 21 . The ouabain-induced model of mania-like behavior in rats is recognized among the employed pharmacological models of mania 22,23 . Also, ICV ouabain administration has an effect on cognitive flexibility and reversal learning in rats 24 .…”
Section: Introductionmentioning
confidence: 99%
“…Another BD-like model has recently been described, based on chronic ouabain treatment 53 . We contend that Valvassori et al's claimed construct and face validity is weaker than ours: decreased Na + /K + -ATPase activity vs. MD in BD (constract); dichotomic use of tests for either mania-or depression-associated behaviors vs. demonstrating both behavioral poles in the same tests (face).…”
Section: The Animal (Mice) Modelmentioning
confidence: 99%
“…Direct ICV ouabain administration will reduce sodium pump activity in the brain (Hamid et al 2009 ), induce both depressive and manic symptoms which can be treated and prevented with lithium (Valvassori et al 2019 ; El-Mallakh et al 1995 ; Li et al 1997 ). The model attempts to mimic the reduced sodium pump activity that has been reported in bipolar illness, not changes in endogenous ouabain.…”
Section: Discussionmentioning
confidence: 99%
“…A similar conclusion is reached when genome wide association studies (GWAS) are explored (Judy and Zandi 2013 ). The only animal models of bipolar illness that meet all validity criteria create ion transport abnormalities (Mack et al 2019 ; Valvassori et al 2019 ). Additionally, nearly all interventions that are effective in mania or mood stabilization reduce intracellular sodium either directly or indirectly (El-Mallakh and Huff 2001 ; El-Mallakh and Paskitti 2001 ; Roberts et al 2010 ).…”
Section: Introductionmentioning
confidence: 99%